Land use impact on potentially toxic metals concentration on surface water and resistant microorganisms in watersheds - Saran, Luciana Maria [UNESP]; Pissarra, Teresa Cristina Tarlé [UNESP]; Silveira, Géssica Aparecida [UNESP]; Constancio, Milena Tavares Lima [UNESP]; de Melo, Wanderley José [UNESP]; Alves, Lúcia Maria Carareto [UNESP] (Elsevier, 2018)
Soil and water resources must be conserved and protected. However, the management of production activities causes a change in the quality of these natural resources due to accumulation in soil of potentially toxic metals. The objective of the present study was to identify the variety and paths of potentially toxic metals (PTMs), such as cadmium, lead, copper, chromium, nickel and zinc, which are associated spatially and temporally to soil and water. We also intended to isolate bacteria resistant to PTMs with important characteristics to be used in bioremediation processes. Water samples were collected every two months for one year (February–December/2014) at eight sites (P1–P8) and the soil samples were collected twice (February and August/2014) from twelve sites (S1–S12). Results indicated that agricultural land use impacts the environment, increasing the concentration of potentially toxic metals, mainly copper, zinc and chromium, in soil and water due to crop management. Ten bacteria resistant to all the metals studied were isolated, which could be used as tools for bioremediation of contaminated soils and water with those metals. The results would positively contribute to land use policy, and for the development of enhanced agricultural practices.
Keywords: Agricultural management; Bioremediation; Environmental degradation; Heavy metals; Soil and water resources; Trace elements